2012
DOI: 10.1007/s00404-012-2560-7
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasive approaches for large ovarian cysts: a careful choice

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a review, Bellati and colleagues mentioned laparoscopically guided minilaparotomy (LGML) in case of benign large adnexal masses, with no other risk factor for malignancy, other than size. They concluded that in terms of safety and feasibility LGML is a better option in comparison to laparoscopy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a review, Bellati and colleagues mentioned laparoscopically guided minilaparotomy (LGML) in case of benign large adnexal masses, with no other risk factor for malignancy, other than size. They concluded that in terms of safety and feasibility LGML is a better option in comparison to laparoscopy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%